AN ANALYSIS OF NARRATIVE STRUCTURALISM IN THE ROAD BY CORMAC McCARTHY’S: AJ GREIMAS PERSPECTIVE - Reffa Pratama; Rezky Khoirina Tarihoran (Fakultas Sastra UMN AL Washliyah, 2023)
The purpose of this study was to find out how the functional scheme works in the story The Road by Cormac McCarthy according to AJ. Greimas. This research was examined using the structuralism theory put forward by AJ. Greimas. The method used is descriptive qualitative to analyze the source of the data taken from quotations in the novel The Road by Cormac McCarthy. The finding in this study is the functional scheme in this story has a stage of telling the subject in reaching the object which opens with an unhappy start, as well as the ending of this story which has a sad ending.